COVID 19: A Surveillance of Symptoms among the Pandemic Affected Population – Online Pilot Survey Study (Advancements in Homeopathic Research, 2022)
Background The world has witnessed Covid 19 pandemic, which has brought a tremendous variations in everybody‘s life. The growing number of sufferers and deaths has created a panic in the people about the well-being of their family members and themselves. For the current pandemic, treatment is predominantly supportive and symptomatic and those who are hospitalized are not sure whether they will return home. Demographic variations are no exemption from getting affected. Objectives • To explore the various clinical presentations of covid 19 affected participants. • To explore possible homoeopathic remedies for therapeutics by means of Repertorisation. Methods The Symptomatology of confirmed Covid 19 cases was compiled through an online “Google form” based survey conducted during October 2020 - May 2021. A pre formed validated questionnaire with voluntary option to participate link was sent via whatsapp to social groups and subjects willing to participate in survey were included. Results 40 subjects participated in this survey. 15 (37.5%) females and 25(62.5%) males participated. Item responses: Fever (52.5%), Dry cough (62.5%), Fatigue (70%), Sputum production (12.5%), Difficulty breathing (22.5%), Sore throat (42.5%), etc. The additional observations included: anxiety /fear of: Recovery (20%), disease (30%), quarantine (17.5%), isolation (5%) and death (7.5%) are observed. Repertorial analysis with hompath wildfire software using complete repertory for the above symptoms, the remedies obtained were: Arsenicum album, Pulsatilla, Calcarea carb, Phosphorus, Sepia, Mercurius, Sulpher, Lycopodium etc. Conclusion General presentation of covid 19 symptomatology and particular symptoms of individuals were obtained and we could explore/investigate certain homoeopathic remedies which reflected the present pandemic disease symptoms and may be used for the management of covid 19 cases by further differentiating them by determinative symptoms of individuals.
Keywords: Covid 19; Homoeopathy; Therapeutics; surveillance of symptoms